Anxiety of reexaminee: a phenomenological study based on the perspective of family life - Nan, Shijie (Transactions on Social Science, Education and Humanities Research, 2024)
In the past decade, the global situation has changed rapidly. The employment situation has been grim year by year and the threshold of academic qualification has been continuously raised, which makes more and more college graduates join the team of postgraduate students, accompanied by the increase in the number of postgraduate students and the emergence of anxiety problems. This paper adopts the qualitative research method and makes a phenomenological analysis of the anxiety problems of 14 postgraduate students from the perspective of family life. It is found that students with multiple anxiety will have an identity crisis and benign parent-child interaction has a positive significance for students with multiple anxiety and obtaining new identity.